Utilisation of the employee health and wellness services at Kimberley Hospital Complex - Mogotsi, Bulelwa Rose (My University, 2012)
Background: The Employee Health and Wellness (EHW) Centre at the Kimberley Hospital Complex (KHC) started off as a staff clinic, rendering nursing services to staff members with occupational injuries and minor ailments such as influenza, colds and headaches. Since the EHW Programme was introduced in 2004 there has been no evaluation of the services provided. There is no information about referrals and current usage of the service, which compromises further planning. Study aim: The aim of the study was to describe the extent and patterns of utilization of the Employee Health and Wellness Services at the Kimberley Hospital Complex for the period 1 January 2008 to 31 December 2009. Methodology: This was a cross sectional descriptive study, involving a retrospective record review at the EHW Centre. Data extraction from various data sources was recorded on data collection tools using coding instead of names to protect the identity of the employees. The study setting was the EHW Centre at Kimberley Hospital Complex, which is the only hospital with a Centre for Employee Health and Wellness in the Northern Cape Province. Conclusion: The utilization rate of the EHW services at KHC is generally low (6.2% and 6.4%) in 2008 and 2009 respectively. There is a need for further research to determine the reasons for low utilisation through employee and employer interviews and focus group discussions. An interesting fact is the steep increase in the number of employees with multiple visits. It would be interesting to conduct a study that will determine the reasons for multiple visits in one month. There was no significant difference between the age and utilization of EHW services but there was a significant association between gender and components of services used, (chi-square test, p<0.001) for both PHC and OHS components. More males used the PHC component whilst more females used the OHS component of the services. While the reasons have not been established, it may possibly be related to a larger number of female employees in the professional category in the health sector. Thus there is a need for further research to explore the gender mismatch in utilising PHC and OHS components of the services. The Wellness programme was minimally used. There was no significant association between age and medical aid status and the usage of service components. The average length of employment for employees who visited the EHW centre was less than 10 years; there was no significant difference in usage of the service between more experienced and less experienced staff. There is a need for further studies to explore reasons for the low utilization rate of the EHW services as well as the perceptions of service providers and employees regarding the utilisation of these services at Kimberley Hospital Complex.
M.P.H., Faculty of Health Sciences, University of the Witwatersrand 2011
Keywords: Occupational Health Services